The disruption of elective procedures due to COVID‑19 in Brazil in 2020 - Frio, Gustavo Saraiva (2022)
Elective procedures were temporarily suspended several times over the course of the pandemic of COVID-19. Monthly data from the Unifed Health System (SUS) were used for the period between January 2008 and December 2020 and the interrupted time series method was used to estimate the efect of the pandemic on the number of elective surgeries and elective procedures that were not performed. Considering a 9-month period, a reduction of 46% in the number of elective procedures carried out in the SUS could be attributed to COVID-19, corresponding to about 828,429 elective procedures cancelled, ranging from 549,921 to 1,106,936. To a full recovery of pre-pandemic performance, SUS would need to increase about 21,362 hospital beds, ranging from 12,370 to 36,392 hospital beds during a 6 month-period. This efort would represent an increase of 8.48% (ranging from 4.91 to 14.45%) in relation to the total number of SUS’s hospital beds in 2019. As a result, the pandemic will leave a large number of elective procedures to be carried out, which will require eforts by health agencies to meet this demand.